Mathematics and arts: Connections between theory and practice in the medieval Islamic world - Özdural, A (Academic Press Inc Elsevier Science, 2000)
Two mathematical sources, On the Geometric Constructions Necessary for the Artisan, by Abu'l-Wafa' (ca. 940-998), and the anonymous work, On Interlocks of Similar or Corresponding Figures (ca. 1300), provide us with insight into the collaboration between mathematicians and artisans in the Islamic world. In this paper I present a series of quotations from these two sources, which show th;lt mathematicians taught geometry to artisans by means of cut-and-paste methods and of geometrical figures that had the potential of being used for ornamental purposes. (C) 2000 Academic Press.
Keywords: Abu 'l-Wafa'; Islamic geometry; Islamic art; mosaics; Abu Bakr al-Khalil